A Gricean Maxim Analysis in English Teaching and Learning Process at English Learning Centre - Musdalipa Dalle; Muh. Hasbi; Aslan Abidin (Universitas Islam Negeri Palopo, 2025)
This study explored the violations from Grice’s cooperative maxims within English language classroom interactions at an English Learning Centre. The research aimed to identify which maxim is most frequently violated and to explain the pragmatic functions of these violations. Applying a qualitative research approach, the researcher examined two audio-recorded classroom sessions: recordings were transcribed and analyzed using interactive analysis (Miles, Huberman, & Saldana). Data underwent reduction, classified under the four Gricean maxims (specifically Quantity, Quality, Relation, Manner), and demonstrated through selected extracts. Finding indicated that breaches of Relation Maxim occurred most often (50%), with Manner (21.42%), Quality (19.04%), and Quantity (9.52%) following in order. Data excerpts indicated that many breaches serve pragmatic purposes to create humor and elicit laughter, maintain rapport, control speaker exchange, and allow self-correction instead of signaling communicative breakdown. The study contended that within informal classroom interaction, dynamic interaction frequently emphasized social interaction instead of rigid information transfer, and that sensitivity of maxim flouting is essential to pragmatic competence. The limitations include a small dataset and lack of reported inter-rater validation. The study closed with a recommendation of explicit pragmatic instruction and future studies utilizing larger samples and verification measures to enhance teaching approaches aimed at fostering pragmatic ability among EFL learners.